Linkage of genes for adult alpha-globin and embryonic alpha-like globin chains. - Whitney, J B (1980)
In alpha-thalassemia, the genetic locus for the alpha chains of adult hemoglobin is not expressed. We have examined the hemoglobins of a number of individual mouse embryos heterozygous for a particular alpha-thalassemia (Hbath-J) and find no decrease in the proportion of hemoglobins containing the alpha chain as compared to the hemoglobin containing the alpha-like embryonic globin chain. This result suggests that the locus for this embryonic alpha-like chain is inactivated or deleted in these embryos as well. Because a single mutational event inactivated adult and embryonic loci, we conclude that they are probably closely linked to one another on the same chromosome. We also present evidence that an unusual hemoglobin in the blood of these embryos is composed only of an embryonic beta-like chain, and is thus analogous to the hemoglobin H (beta 4 tetramer) of adult alpha-thalassemics.